Pleopeltis glandulosa (Polypodiales: Polypodiaceae), a new species from the Prepuna district of Monte biogeographic province in Argentina - Arana, Marcelo D.; Slanis, Alberto; Bulacio, Eva (Phytotaxa, 2024)
Pleopeltis glandulosa sp. nov. (Polypodiaceae) is described as new species from the Prepuna, a xeric environment dominated by columnar Cactaceae of the biogeographic province Monte. It is characterised by having laminar bases truncate, adaxially glabrous and abaxially completely covered with scales, the scales margins with glandular papillae, and the apices filiform, with a conspicuous glandular apical cell with mucilage. Morphologically, P. glandulosa most resembles P. thyssanolepis, not recorded till the moment in Argentinian flora, but widespread from Mexico to Bolivia, because of its strongly bicolorous rhizome scales, pinnatifid laminae with the abaxial surface covered by scales, and obscure veins, but differs mainly by the glandular trichomes at the margins of rhizomatic scales, and laminar scales with glandular papillae at the margins and the conspicuous glandular apical cell, the alate stipes, and the inconspicuous hydathodes.